USM – PNU TO EXPAND COLLABORATION WITH EXCHANGE PROGRAMMES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 June 2016 Universiti Sains Malaysia (USM) is going to expand collaborations with Princess of Naradhiwas University Thailand (PNU), as a result of the visit by the delegates from PNU to USM today.